GTSE1 Facilitates the Malignant Phenotype of Lung Cancer Cells via Activating AKT/mTOR Signaling - Fan Zhang; Jingfei Meng; Hong Jiang; Xing Feng; Dongshan Wei; Wen Meng (Analytical Cellular Pathology)
The expression of G2 and S phase-expressed-1 (GTSE1) was upregulated in human cancer. However, its expression and roles in lung cancer have not been identified yet. In our study, we reported that GTSE1 expression was statistically higher in lung tissues than in the adjacent noncancerous tissues which might be a consequence of hypomethylation of the GTSE1 promoter. The upregulated expression of GTSE1 mRNA predicted the poorer survival of the lung patients. Ectopic expression of GTSE1 in lung cancer cells significantly increased while knockdown of GTSE1 decreased cell proliferation, cell migration, and cell invasion in H460 and A549 cells. Furthermore, knockdown of GTSE1 regulated the cell cycle and promoted cell apoptosis in H460 and A549 cells. Finally, we presented that GTSE1 was able to activate AKT/mTOR signaling in H460 and A549 cells. In conclusion, these results indicated that the overexpressed GTSE1 was involved in the progress of lung cancer by promoting proliferation migration and invasion and inhibiting apoptosis of lung cancer cells via activating AKT/mTOR signaling.